A review of evidence on the link between masculinity, loneliness, and suicide as observed in social media discussions - Freddie Jones; Lily Verity; Margarita Panayiotou; Pamela Qualter (Current Research in Behavioral Sciences, 2023)
This review explores qualitative studies that examined the relationship between loneliness and suicide among young men (18–25 years) as it is discussed on social media. In the 8 papers we identified, analyses validated the relationship between loneliness and suicide in social media discourses. The findings also show that attitudes towards masculinity and mental health prevent some men from discussing mental health issues, which increases loneliness; other men had opportunities to share their experiences openly, breaking preconceived gender rules. Thus, the conceptualizations of gender appeared to affect individuals' expression of their mental health online, with traditional masculine ideals seemingly restricting individuals from reaching out for support, increasing loneliness. Papers often discussed how gender norms negatively impacted the degree to which men felt their mental health issues and loneliness were ‘tellable’. However, there was emerging evidence that some online platforms permitted tellability of men's mental health and loneliness issues. This review highlights the close relationship between loneliness and mental health, and how both are affected by all masculinities.